An Investigation of the Correlation of Lectures Personality and Students Reading Achievement in Learning Reading Comprehension - Yukir, Muh. (Maspul Journal of English Studies, 2023)
The study aims primarily at finding out the empirical description of the correlation between lecturers’ personality and the students’ reading achievement and the influence of lecturer personality toward students’ achievement in reading course. The problem statements are there correlation between lectures personality and the students reading achievement, and how is the influence of lecturer personality toward students’ achievement in reading course. Using descriptive method approach in analyzing and collecting the data to explain how the lectures personality influence student’s achievement in learning reading course. It also focused on the correlation between lecturer’s personality and the student’s achievement in learning reading comprehension. In this research, the data collecting by using questionnaire to find out the percentage of the lecturer’s personality which influence student’s achievement in learning reading course. The result reveal that the correlation between lecturer teaches reading course and students achievement is medium correlation (0.40). The result of analysis shows that T. test is (60.7225) ≥ T. table (55.76), it indicates the lecturers’ personality influence toward student’s achievement in learning reading course. Generally, the study validates how lecturer’s personality influences English students’ achievement as intervened by the academic language education.